2023
DOI: 10.1186/s40337-023-00776-1
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of anxiety and depression between problematic social media use and bulimia nervosa among Lebanese university students

Abstract: Background Bulimia nervosa (BN) is a disorder that is characterized by binge eating and inappropriate compensatory behavior to control weight. The aim of this study was to evaluate the mediating role of anxiety and depression between problematic social media use (PSMU) and BN among a sample of Lebanese university students. Methods This cross-sectional study was carried out between July and September 2021; a total of 363 university students was recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…Among Italian college students, there was a positive significant correlation between the levels of PA and frequency of neck and low back pain, where low PA levels were associated with musculoskeletal pain onset and pain worsening, and PA of < 150 min/week predisposed students to neck and low back pain (OR = 1.95, 95% CI: 1.44-2.64 and OR = 1.79, 95% CI: 1.29-2.49, respectively) (2). Similarly, higher depression and anxiety were associated with more bulimia nervosa (18).…”
Section: Introductionmentioning
confidence: 90%
“…Among Italian college students, there was a positive significant correlation between the levels of PA and frequency of neck and low back pain, where low PA levels were associated with musculoskeletal pain onset and pain worsening, and PA of < 150 min/week predisposed students to neck and low back pain (OR = 1.95, 95% CI: 1.44-2.64 and OR = 1.79, 95% CI: 1.29-2.49, respectively) (2). Similarly, higher depression and anxiety were associated with more bulimia nervosa (18).…”
Section: Introductionmentioning
confidence: 90%
“…The fact that no physical activities are involved contributes to the student developing a slothful attitude. It has also been observed that, in many instances, students start giving up their sleep and develop severe cases of sleeping disorders (Alismaiel, 2023;Sfeir et al, 2023;Lederman, 2023).…”
Section: Students' Use Of Social Media Can Pose Grave Health Risksmentioning
confidence: 99%